EXPERIMENTAL INVESTIGATION OF CUTTING FORCES IN ORTHOGONAL CUTTING USING ROUNDED EDGE WORN TOOL - Uysal, Alper; Altan, Erhan d (YILDIZ TECHNICAL UNIV, 2013)
Cutting tools used in machining operations have slight roundness on the cutting edge regardless of their manufacturing methods. In some cases, edge of the cutting tool is specially rounded. In this study, effects of flank wear rate, cutting edge radius, uncut chip thickness, cutting speed and rake angle on cutting force, thrust force and resultant force were experimentally investigated in orthogonal cutting operations. Cutting tools having 50 mu m, 125 mu m and 200 mu m flank wear rates and 50 mu m, 100 mu m and 150 mu m cutting edge radii were used in experiments carried out by using quick-stop orthogonal cutting device. Experiments were carried out at three different uncut chip thicknesses ( 100 mu m, 150 mu m and 200 mu m) and cutting speeds (0,25 m/ dak, 0,5 m/ dak and 0,75 m/ dak) and two different rake angles (2 degrees and 6 degrees) and effects of flank wear rate, cutting edge radius and cutting parameters on cutting forces were determined. Cutting forces increased when flank wear rate, cutting edge radius and uncut chip thickness increased and slightly decreased when cutting speed and rake angle increased. Besides, micro views of the samples obtained from quick-stop device were analyzed and the effects of flank wear rate on dead metal zone formed in front of the tool were investigated. It was seen that dead metal zone became smaller when flank wear rate increased.
Keywords: Rounded edge worn tool; cutting forces; dead metal zone; Engineering